Comparative Study on Electrochemical Treatment of Cyanide Wastewater - Lei, Siming; Song, Yonghui (Frontiers in Chemistry, 2021)
In this paper, two-dimensional(2D) and three-dimensional(3D) electrochemical systems were used to treat cyanide wastewater. The effect of the applied voltage and the material of the main electrode on the removal of various ions and the characteristics of chemical reactions were mainly studied. The shape, load substances, and precipitate characteristics of the electrode plates were analyzed by scanning electron microscopy and energy spectrum and X-ray diffraction. The results show that the applied voltage was the key effect factor in the electrochemical treatment process. The removal of ions on the wastewater at 2V were mainly due to the effect of electro adsorption and enrichment precipitation, while at 4V, it is mainly due to anodization and cathodic deposition. The treatment effect of 3D electrode system was significantly better than that of the corresponding 2D system. The treatment effect of 3D electrode system with granular activated carbon as the particle electrode, activated carbon filled stainless steel mesh (CM) and coal based electrode (CB) as the main electrode are better than that with stainless steel mesh (M). In the 3D system, CB as the main electrode, with the applied voltage of 4V, the treatment time of 5h, the plate spacing of 10 mm, and the dosage of activated carbon particles of 2g, and the removal rates of CNT, Cu, Zn, CN- and SCN- were 94.14%, 94.53%, 98.14%, 98.55% and 93.13%, respectively. At this time, the electrolytic oxidation reaction of CN- and SCN- was the main reaction of anode, while the electrolytic deposition of Cu, Zn and other metal ions was the main reaction of cathode surface. There were not only adsorption and electric adsorption of various ions, but also electrolytic deposition reaction of Cu, Zn and other metal ions on the surface of activated carbon particle electrode. In the process of electrochemical reaction, the concentration of hydrogen ions near the anode increases locally, which results in producing the precipitation of CuSCN, Cu2Fe(CN)6, Zn2Fe(CN)6 etc. in the solution, which is also helpful for the removal of cyanide and heavy metal ions in cyanide wastewater.